Plasma formation induced by a Q-switched Nd:YAG laser - Ali, Ahmad Hadi; Bidin, Noriah (Institut Fizik Malaysia, 2004)
Light energy can create a plasma when high irradiance is focused. This proeess of opticical breakdown can be achieved by using a Q-switched laser. In this paper, we report the application of a high-power Nd:YAG laser to generate plasma. Two different techniques were conducted to generate optical breakdown and initiate the plasma. In the first technique the laser was diverged by a negative lens and brought to focus by a wide-angle camera lens of 28 mm focal length. Secondly, the same concave lens was employed to expand the beam but converged back by using a longer focal length of 50 mm. The plasma formation from both focusing systems are visualized and recorded via CCD video camera in conjunction with a high-speed photography system. The recorded images were analyzed using the Matrox Inspector version 2.1 software. The maximum plasma length obtained from short and long focal length system are 1.193 ± 0.060 mm and 2.815 ± 0.141 mm respectively. Nevertheless, both techniques produced broadly elliptical shape of plasma and exponentially expand with respect to the increasing of laser power.